Pengaruh Media Benda Konkret Terhadap Hasil Belajar IPA Siswa Kelas V SDN 091538 Huta Bayu Raja - Ristika Ulyartha Silalahi; Natalina Purba; Maria Barus (CV Putra Publisher, 2024)
The aim of this research is to find out whether concrete object media influences the science learning outcomes of class V students at SDN 091538 Huta Bayu Raja or not. There are 2 hypotheses in this research, namely, (1) there is an influence of the use of concrete object media on the learning outcomes of fifth grade students at SDN 091538 Huta Bayu Raja (Ha) and (2) there is no influence of the use of concrete object media on the science learning outcomes of fifth grade students at SDN 091538 Huta Bayu Raja (H0). This research method is an experimental method with a Pre-Experimental Design type of research using the